Incorporation of Pt–Cr nanoparticles into highly porous MOF-5 as efficient oxygen reduction electrocatalysts. (13th August 2020) - Parkash, Anand
Abstract: Developing new materials that can enhance the efficiency of energy conversion and storage systems is critical to meeting the rising energy demand of low-carbon economies. Mesoporous materials have the advantages of large specific surface area and multiple channels, which can increase efficiency and flexibility in terms of energy and power density. An active catalyst for oxygen reduction reaction (ORR) based on Pt–Cr nanoparticles with ultralow Pt content (0.90 wt%) has been studied in this paper. In contrast, electrocatalyst Pt/Cr/NPC-900 exhibited an ORR activity with onset potential ( E o ) of 1.01 V vs. RHE in an alkaline solution that was superior to commercial Pt/C (20 wt%) (0.96 V vs. RHE). The presence of metal oxides and optimal Pt content enhanced the ORR activity. Therefore, the synergistic effect of the high surface area increased charge transfer, and excellent structural stability can achieve significant ORR efficiency, which is conducive to excellent activity. These findings provide a new perspective for economical and practical ORR electrocatalysts to be designed and synthesized rationally.